Innovation Model of Licensing Service SIMPATIK JABAR (Licensing Service Information System for the People of West Java) - Nurhakim Ramdani Fauzian (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2021)
The research describes the licensing service innovation model called SIMPATIK JABAR (Licensing Service Information System for the People of West Java) at the Investment and One Stop Service Office of West Java Province. The research was based on the finding that the implementation of SIMPATIK JABAR innovation did not contribute much in elevating the quality of public services at the Investment and One Stop Service Office of West Java Province. This can be seen from the unsatisfactory Public Satisfaction Index over the public service delivery at the Investment and One Stop Service Office of West Java Province, especially due to sluggish licensing service completion. The research employed a qualitative method. The data were obtained through document reviews, observations, and in-depth interviews to 16 (sixteen) informants. Referring to the analysis results, a form of innovation development was formulated by using the approach of USAID Innovation Development Process.Based on the research findings, it is recommended that the implementation of the SIMPATIK JABAR innovation model introduce an improvement in the form of the human resource management for the Technical Team of One Stop Service (PTSP). This can be done by recruiting experts/academicians to become members of the Technical Team. The experts/academicians then collaborate with the civil servants of West Java Provincial Government assigned as the Technical Team to formulate the licensing technical considerations. It is expected that the involvement of experts/academicians at the PTSP Technical Team can help resolve technical recommendations more quickly, so that it can improve the quality of public services at the Investment and One Stop Service Office of West Java Province.